Legal Services Virtual Couple Rental Perspective Wahbah Az Zuhaili - Kartika, Chairany; Yazid, Imam (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
Islam regulates the various wages of human life, including rent to rent in order to take place with benefits that are in accordance with the goals of sharia. The problem is known to exist virtual couple rental practices that offer dating services for its clients. This paper is to find out how to practice virtual couple rental through social media, and to find out the law based on Wahbah az-Zuhaili perspective. This research is juridical-normative research with a conceptual approach. The theory used as a knife of analysis is the theory of the observance of law. This study found first, the practice of virtual partner rental business through social media can be done by looking at posts about various types of service offerings provided by virtual partner rental business account owners with a set price that is adjusted to the right time desired and clearly defined on the homepage of the account. So, each client is not mistaken about every service provided along with the nominal price to be paid. Second, although at a glance this practice meets the pillars of Ijarah on Wahbah az-Zuhaili and has a clear wage system this practice violates one of the conditions in the form of a work object, which is, where the object of work on this practice is concluded not in accordance Sharia because 85.7% of users choose partners who are against the type so it is likely that the object of this practice is not in accordance with Sharia and banned. Prophet Muhammad SAW said that means ‘It should not be between a man and a woman alone unless accompanied by his muhrim, and a woman should not travel unless accompanied by his mahram. Because it can bring closer to the deeds of adultery.